Electrochemical Assessment of Thiazolidine Derivative as a Corrosion Suppressant for Carbon Steel in Acidic Medium (The International Journal for Scientific Research, 2025)
A thiazolidine-based compound (AS6) was synthesized and structurally confirmed through Fourier-transform infrared spectroscopy (FT-IR) and proton nuclear magnetic resonance (¹H-NMR) techniques. Its potential as a corrosion inhibitor for N80 carbon steel in a 1 M hydrochloric acid environment was systematically investigated. The study involved electrochemical assessments, adsorption modeling, activation energy calculations, and surface characterization using Tafel polarization, Langmuir isotherms, the Arrhenius approach, and scanning electron microscopy (SEM) coupled with energy-dispersive spectroscopy (EDS). The results revealed a notable enhancement in inhibition efficiency at elevated inhibitor concentrations, while higher temperatures led to a decline in performance. Tafel polarization data demonstrated a consistent reduction in corrosion rate as the inhibitor concentration increased. Surface analysis confirmed the development of a protective film on the steel substrate, highlighting the practical applicability of AS6 in industrial corrosion mitigation.